Effect of Temperature and Steam-to-Carbon Monoxide (CO) Ratio on Hydrogen Production in Water-Gas Shift Reaction using Cu-ZnO-Al2O3 Catalyst - Desi, Sekar Kumala; Nursa'adah, Restu Siti; Anindita, Hana Nabila; Muharto, Bambang; Rahmawati, Nurdiah; Rini, Tyas Puspita; Rosyadi, Erlan (Makara Journal of Science, 2023)
This study investigates the effect of steam-to-CO molar ratio and temperature on hydrogen production in a water gas shift reaction using a Cu-ZnO-Al2O3 catalyst. Herein, different steam-to-CO molar ratios (1:1, 2:1, and 3:1) and temperatures (200 °C, 250 °C, and 300 °C) were applied to investigate their impact on the reaction and H2 production. The Cu-ZnO-Al2O3 catalyst was characterized by its surface area, pore size distribution, and chemical composition. Moreover, the experimental setup enabled the control of temperature and steam-to-CO molar ratio while monitoring the product gas composition. The results revealed a considerable influence of temperature and steam-to-CO molar ratio on CO conversion efficiency. Notably, the majority of the experiment variations exhibited CO conversion exceeding 90% within 1 min throughout the reaction. Additionally, the highest H2 composition of 53.10% was reached at 250 °C with the steam-to-CO molar ratio of 3:1.